Intentionality, anger, coping, and ego defensiveness in reactive aggressive driving. Issue 5 (12th February 2014) - Vallières, Evelyne F.; Vallerand, Robert J.; Bergeron, Jacques; McDuff, Pierre
Abstract A motivational sequence was used as a theoretical framework for studying reactive aggressive driving. Study 1 tested the validity of the sequence "perceived intentionality‐anger‐reactive aggressive driving" and assessed the impact of coping on anger and reactive aggressive driving. The ecological validity of the same sequence was verified in Study 2 with a large sample of adult drivers, while examining the role of ego defensiveness as a determinant of anger and aggressive driving. Study 1 showed the proposed sequence was supported and that coping strategies intervened at both anger and reaction levels, depending if the situation was perceived as intentional or not. Study 2 showed that anger mediated the impact of coping and ego defensiveness on driving aggression. Sobel tests confirmed the anger mediation effect in both studies.